2015
DOI: 10.2139/ssrn.2698290
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Exceptionalism? Performance and Allocation in the U.S. Healthcare Sector

Abstract: The conventional wisdom for the healthcare sector is that idiosyncratic features leave little scope for market forces to allocate consumers to higher performance producers. However, we find robust evidence -across several different conditions and performance measures -that higher quality hospitals have higher market shares and grow more over time. The relationship between performance and allocation is stronger among patients who have greater scope for hospital choice, suggesting that patient demand plays an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 81 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…Moving a patient to a provider that would increase her 30-day survival probability by one percentage point places her in a hospital with 1.9% higher spending and 4.3% higher Medicare patient volume, on average. These results are qualitatively similar to what earlier work has found when measuring quality by observational RAMs (Foster et al, 2013;Chandra et al, 2015;Doyle et al, 2015). However, consistent with a broad pattern of better hospitals attracting sicker patients, I show that the strength of these relationships is magnified when they are measured with quasi-experimental data.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moving a patient to a provider that would increase her 30-day survival probability by one percentage point places her in a hospital with 1.9% higher spending and 4.3% higher Medicare patient volume, on average. These results are qualitatively similar to what earlier work has found when measuring quality by observational RAMs (Foster et al, 2013;Chandra et al, 2015;Doyle et al, 2015). However, consistent with a broad pattern of better hospitals attracting sicker patients, I show that the strength of these relationships is magnified when they are measured with quasi-experimental data.…”
Section: Introductionsupporting
confidence: 90%
“…Hospitals with low risk-adjusted mortality rates, for example, are now rewarded with higher Medicare reimbursement rates, while providers with poor survival outcomes may be flagged as low-performers. Recent research has found that such quality-based policies shape both hospital incentives and patient admission patterns (Norton et al, 2016;Gupta, 2016;Dranove and Sfekas, 2008;Chandra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Texas Higher Education Coordinating Board Enrollment Variables: We code a student as having enrolled in college if she ever attends a school in the THECB data. Two-year and four-year college results are coded similarly.…”
Section: Texas Education Agencymentioning
confidence: 99%
“…Determination of special education or ELL status is done by HISD Special Education Services and the HISD Language Proficiency Assessment Committee. 17 Texas Education Code Section 29.081 defines a student as at-risk of dropping out if any of the following is true: (1) the student was held back in one grade level; (2) the student is in grades 7-12, did not maintain an average equivalent to 70 on a scale of 100 in two or more subjects in the foundation curriculum during a semester in the preceding or current school year, or is not maintaining such an average in two or more subjects in the foundation curriculum in the current semester; (3) did not perform satisfactorily on an assessment, and who has not in the previous or current school year subsequently performed on that instrument or another appropriate instrument at a level equal to at least 110 percent of the level of satisfactory performance on that instrument; (4) if the student is in PK-3 and did not perform satisfactorily on a readiness test or assessment instrument administered during the current school year; (5) is pregnant or is a parent; (6) has been placed in an alternative education program during the preceding or current school year; (7) has been expelled during the preceding or current school year; (8) is currently on parole, probation, deferred prosecution, or other conditional release; (9) was previously reported as having dropped out of school; (10) is a student of limited English proficiency; (11) is in the custody or care of the Department of Protective and Regulatory Services or has been referred to the department during the current school year; (12) is homeless; or (13) currently or in the past school year resided in a residential placement facility.…”
Section: Texas Workforce Commissionmentioning
confidence: 99%
“…A quotidian feature of health-care systems is the presence of substantial variations in productivity. 1 Figure 1 shows the distribution of both total factor productivity (TFP) and labor productivity adjusted for cost across NHS hospital trusts; a trust consists of one or more hospital sites. The productivity data were obtained from a previous study, 2 spanning the period 2010/11 to 2012/13.…”
Section: Introductionmentioning
confidence: 99%